Impact and treatment of cancer during pregnancy. Issue 5 (1st October 2004) - Weisz, Boaz; Meirow, Dror; Schiff, Eyal; Lishner, Michael
Cancer is the second most common cause of death in the reproductive years and complicates up to one in 1000 pregnancies. When cancer is diagnosed during pregnancy, the management strategy must take into account both the mother and developing fetus. In this article, the four most common malignancies diagnosed in pregnant patients –– cervical and breast cancer, malignant melanoma and lymphoma –– will be reviewed, with an emphasis on the impact of the diagnosis and management on the pregnant patient and the developing fetus.